Effect of different rootstocks and scion ages on the productivity of screenhouse grown tomato (Solanum lycopersicum) - Cacayurin, Christian Agas; Cacal, Darwin Marzan; Ronquillo, Shelah Ramirez (Journal of Asian Scientific Research, 2024)
This study aimed to assess the impact of utilizing diverse rootstocks grafted with scions of varying ages on the growth, yield, and fruit quality of tomatoes. Employing a Completely Randomized Design (CRD), the experiment featured three replications per treatment in a two-factor design. Results revealed that a 30-day-old scion exhibited a highly significant difference in tomato height gain at 15 and 30 days after transplanting (DAT) and statistically mirrored the performance of a 21-day-old scion at 60 DAT. A 25-day-old scion grafted onto wild eggplant demonstrated the greatest height gain among grafts but did not surpass the height of non-grafted tomatoes. Notably, the 30-day-old scion significantly influenced tomato height at 15 and 30 DAT. The 25-day-old scion of wild eggplant exhibited the highest height gain but failed to surpass the non-grafted tomatoes. A 21-day-old scion of eggplant yielded the highest plant and 240 sqm-based tomato yields. Interaction analysis revealed that a 30-day-old scion of eggplant produced the highest yield. Additionally, the 25-day-old scion of wild eggplant resulted in the largest fruit diameter, while the 21-day-old scion of black nightshade displayed the highest sugar content. Different scion and rootstock combinations yielded varying percentages of fruit color. Optimal profitability was achieved with a 30-day-old scion of eggplant, offering the highest net income, while the highest return on investment (ROI) was achieved with a 21-day-old scion of wild eggplant. Findings emphasize the importance of carefully selecting scion age and rootstock combinations to optimize tomato growth, yield, and quality, ultimately enhancing profitability in tomato cultivation.